Predicting relapse after achieving a functional cure for chronic hepatitis B (CHB) using baseline HBsAg and end-of-treatment HBsAb levels - Lianxiu Han; Zilong Wang; Luyang Kang; Xiaoling Cui; Yi Li; Huafa Yin; Yufeng Gao; Jiabin Li (Scientific Reports)
Abstract Among the factors influencing relapse after clinical cure of chronic hepatitis B(CHB). There is no standardization of baseline HBsAg levels and end-of-treatment HBsAb levels. This multicenter, retrospective study enrolled 136 patients who achieved functional cure from June 2019 to December 2023, and a total of 48 weeks of follow-up was conducted after treatment cessation according to the CHB guidelines. Baseline characteristics of patients were analyzed using univariates. Multifactorial logistic regression was used to analyze the different levels of HBsAg at baseline and HBsAb at the end of treatment in CHB recurrence. The working characteristic curve of the subject was constructed and observed by the column line graphical prediction model. Our data showed the cumulative recurrence rate using Kaplan-Meier survival analysis. At baseline, the level of HBsAg was significantly greater in the group with recurrence than in the group without recurrence (P = 0.038). At EOT, HBsAb levels were lower in the relapsed group than in the nonrelapsed group (P = 0.014). Multivariate logistic regression analysis revealed that a baseline serum HBsAg concentration ≥ 100 IU/mL was a risk factor for recurrence, and an EOT serum HBsAb concentration ≥ 500 mIU/mL was a protective factor for recurrence. Kaplan-Meier survival analysis showed relapse rates of 3.8% and 12.2% for HBsAg ≤ 100 IU/mL at baseline and HBsAb ≥ 500 mIU/mL at the end of treatment, respectively. Functionally cured patients with CHB when baseline HBsAg ≤ 100 IU/mL and HBsAb ≥ 500 mIU/mL at the end of treatment have a low relapse rate.